2012
DOI: 10.1007/s00404-012-2419-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic temporary clipping of uterine artery during laparoscopic myomectomy

Abstract: The use of the clips has proved to be statistically effective in reducing hemoglobin loss during laparoscopic myomectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Different management strategies during laparoscopic myomectomy have been described, such as using vascular clips or silk sutures for occlusion of the uterine arteries or bipolar coagulation of the uterine vessels before laparoscopic myomectomy . However, the use of permanent embolic materials in women who desire future fertility is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different management strategies during laparoscopic myomectomy have been described, such as using vascular clips or silk sutures for occlusion of the uterine arteries or bipolar coagulation of the uterine vessels before laparoscopic myomectomy . However, the use of permanent embolic materials in women who desire future fertility is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Different management strategies during laparoscopic myomectomy have been described, such as using vascular clips or silk sutures for occlusion of the uterine arteries or bipolar coagulation of the uterine vessels before laparoscopic myomectomy. [26][27][28] However, the use of permanent embolic materials in women who desire future fertility is controversial. They may have a significantly increased risk for blood supply issues, resulting in potential ischemic complications involving the uterus and ovaries, and adverse long-term effects on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prospective studies have found that both suture ligation and vascular clip application at the uterine arteries significantly reduced EBL (MD: À94 to À229 mL) without a significant impact on fertility outcomes. [132][133][134][135][136] De novo adhesion formation after LM averages 41.3% and can have a significant impact on future fertility. 137 Aside from optimal surgical technique and hemostasis, several adhesion barriers are available in the United States for adhesion prevention.…”
Section: Preoperative Treatmentmentioning
confidence: 99%
“…Vaginal access in this midline approach is limited which makes uterine manipulation diffi cult. Clipping of uterine vessels is another method shown to effectively reduce blood loss during the procedure (Sinha et al 2004 ;Vercellino et al 2012 ;Rosen et al 2009 ). With side docking, the robot is positioned at the left or right patient's knee at a 45° angle from the lower torso ( Fig.…”
Section: Tips and Techniquesmentioning
confidence: 99%